On the convergence of discrete optimum control process to its continuous analogue - Bistrickas, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Бистрицкас. К вопросу о сходимости дискретного процесса оптимального управления к непрерывномуV. Bistrickas. Diskretinio optimalaus valdymo proceso konvergencijos į tolydinį klausimu